Impact Of Subsidy Removal On School Administration, Teachers Job Performance And Students’ Academic Performance In Secondary Schools In Nigeria - Niyi Jacob Ogunode; Dr. Olofu, Paul Agbade (International Journal on Integrated Education, 2023)
This paper assessed the impact of subsidy removal on school administration, teacher’s job performance and students’ academic performance in secondary schools in FCT, Abuja. Secondary data were used in the paper and the data were collected from both print and online publications. The paper concluded that subsidy removal in Nigeria have led to increment in operational cost of running schools, affected teachers job performance and students’ academic performance. Based on these findings, the paper recommended the following. Government should increase budgetary allocation to all secondary schools in FCT and in Nigeria at large. This will help school administrators to meet up with the operational running cost of running the schools. Government should provide school buses to all secondary schools in FCT and in Nigeria at large to aid teachers and students movement to schools. Government should provide instructional materials like textbooks, calculators, exercise books, drawing aids to students.